DEFENSE FINANCING FEATURES WITHIN THE CONTEXT OF THE NEW CHALLENGES (Globalization and Business, 2023)
The beginning of the third millennium was marked by the desire of the leader countries (USA, China, and Russia) to geopolitical, geostrategic and geo-economic redistribution of spheres of influence. The collapse of the USSR, the dissolution of the Warsaw Pact Organization, the end of the Cold War did not bring the world closer to stability and security. Military force capabilities continue to be considered as one of the most powerful factors in world politics. Proof of this is the intensification of the struggle of the world's superpowers for regional and global leadership, control over oil, gas and energy flows. It is worth mentioning the Transnistrian conflict, Russia-Led wars in South Ossetia and Abkhazia, the Russian-Georgian war in August 2008, the civil war in Syria, the intensification of Islamic extremism within the ISIS, Russia's annexation of Crimea, the hybrid war unleashed and continues to wage by the Russian Federation against Ukraine. In this connection, it is becoming increasingly important to provide corresponding levels for the defense budget funding. Thus, the study of the peculiarities of defense financing in Ukraine and powerful military superpowers is of considerable scientific, practical and political interest. Comparing the defense expenditures of different countries makes it possible to identify key problem issues in the defense financing of Ukraine and bring the corresponding costs to international standards. This indicator is one of the most important criteria that characterize the state's desire for development, relevant combat readiness of the armed forces and other military forces in the face of new challenges.  The last years of the previous century were characterized by global geopolitical changes and growing contradictions, which resulted in: the transformation of the bipolar model (USA - USSR) into a multipolar (powerful military superpowers - the USA, Russia, China, Saudi Arabia, France, Japan, Germany, India, Brazil)); globalization of world economic processes; erosion through "hybrid wars", which are a new kind of global confrontation in today's destabilized international security environment, the facets of the division between war and peace.  The availability of weapons of mass destruction and high-precision weapons in the third millennium, the growth of their capacity, the complexity of military equipment and combat assets, the use of new methods and means of warfare have led to significant changes in the functions and tasks of the armed forces, increasing their number and government spending on defense purposes. Today there are about 200 armies in the world with a total number of 24-25 million people (about 0.4% of the world's population) (Military..., 2002). The state of the troops of any state must correspond to its economic capabilities and at the same time ensure the implementation of national security tasks.